Structural, optical, and electrical reinforcement of gamma-irradiated PEO/SA/Au NPs nanocomposite - Abdelghany, A. M.; Farea, M. O.; Oraby, A. H. (Journal of materials science. Materials in electronics, 2021)
Gold nanoparticles have been successfully green synthesized using Chenopodium murale leaf. Composite films of sodium alginate (SA) and polyethylene oxide (PEO) containing different contents of gold nanoparticles (Au NPs) in the doping level in combination with their virgin samples were prepared via ordinary solution casting routine. Synthesized nanocomposite thin films were studied before and after being exposed to successive doses of gamma irradiation (2, 4, 6 Mrad). X-ray diffraction depicted the semi-crystalline nature of studied nanocomposites that decreased through both embedding Au NPs and successive irradiation doses. FTIR spectra displayed the interactions and variations within the functional groups of their corresponding pristine components and dopant nano-fillers. Ultraviolet visible (UV/Vis) spectroscopy revealed the existence of a n–π* transition resulting from single bond discerned within the backbone of PEO/SA and exhibited a visible band at 526 nm, attributed for the surface plasmon resonance of Au NPs affected with irradiation doses. TEM micrograph exhibited Au NPs spherically shaped with size depends on the irradiation doses. The electrical conductivity in combination with dielectric permittivity (ɛ′) and dielectric losses (ε″) of synthesized composite films was found to be affected by gamma irradiation.